(untitled) (Applied Biological Research, 2019)
Capsicum annuum L. var. grossum is the most widely cultivated species of pepper which finds use in culinary and medicinal industry. Genetic divergence among 20 germplasm, collected from diverse locations of India, was estimated on 18 morphological, growth and chemotypic characteristics. Based on above characterization, the genotypes were grouped into 7 clusters. Cluster II had maximum number of genotypes (06), followed by Cluster I and III (4 each) and IV (3); whereas cluster V, VI and VII had only one genotype each. The highest (35.91) inter-cluster distance was observed between cluster VI and VII and lowest (12.66) between cluster I and II. Cluster IV (D2 24.35) exhibited highest intra-cluster distance whereas cluster I had lowest intra-cluster distance (D2 6.28). On the basis of cluster means, genotypes viz., ‘CITH-M-SP-12’,‘UHF-1’ and ‘SP-461’ contributed maximum towards genetic divergence for high ascorbic acid content, TSS, reducing and total sugars content. Considering diversity pattern and other horticultural performance, ‘CITH-M-SP-2’ from cluster VI may be considered as one of the better parents in hybridization programme for most growth and yield parameters.